Soil erosion assessment in the agricultural microbasin of Pito Aceso in the municipality of Bom Jardim, Rio de Janeiro State. - JAVIER NUÑEZ, J. (2010)
In rural areas inappropriate land use generates soil problems such as soil particles dissociation, reduction of soil fertility and agriculture productivity. For the Serrano Region of Brazil the mixture of natural and anthropogenic processes such as high precipitation regimens, very steeped relief, deforestation, and agriculture in slopes are predominant factors that enhance these soil problems. The objective of this research is to assess the landscape vulnerability to water erosion of the agricultural micro-basin of Pito Aceso in the Municipality of Bon Jardim in the State of Rio de Janeiro. The research is divided in two parts: a) A desk research: which consists of a literature review, generation and interpretation digital maps and; b) A field assessment: which consists of the identification of different types of: a) Soil erosion; b) Support practices and; c) Crop and cover management tendencies. Results indicates that Pito Aceso presents a rough relief with moderate to severe erosion in areas dominated by clean pastures (CP), moderate erosion in areas under annual (AC) and perennial cropping (PC) and light erosion in areas under forest. Also it is found that in Pito Aceso the more vulnerable areas to erosion are areas in Cambisols and Latosols under CP and AC in slope with very strong, strong and medium gradient, followed by areas under PC with very strong and strong gradient. In general Pito Aceso presents a rough relief which demands a careful land use planning and the adoption of soil conservation practices.